2013
DOI: 10.3928/01477447-20131021-17
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Interference Screw and Cortical Button With Screw Hybrid Technique for Distal Biceps Brachii Tendon Repair

Abstract: Various fixation techniques have been described for ruptured distal biceps tendons. The authors hypothesized that no significant differences would be found between the mean failure strength, maximum strength, and stiffness of the interference screw and hybrid technique. Fourteen fresh-frozen human cadaveric elbows were prepared. Specimens were randomized to either interference screw or hybrid cortical button with screw fixation. The tendon was pulled at a rate of 4 mm/s until failure. Failure strength, maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The addition of an interference screw has been shown to produce a more anatomic placement of the repaired biceps tendon but has not been shown to lead to significant improvement in biomechanical strength compared with button alone. 1,31,33 Further research is warranted to determine if the quicker release from medical care with cortical button plus interference screw observed in our cohort equates to a significantly sooner return to work compared with the other repair methods. The trend in repair techniques as seen in Figures 1 and 2 demonstrates a decline in doubleincision repairs and an increase in cortical button alone and cortical button plus interference screw fixation over the course of our study period.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The addition of an interference screw has been shown to produce a more anatomic placement of the repaired biceps tendon but has not been shown to lead to significant improvement in biomechanical strength compared with button alone. 1,31,33 Further research is warranted to determine if the quicker release from medical care with cortical button plus interference screw observed in our cohort equates to a significantly sooner return to work compared with the other repair methods. The trend in repair techniques as seen in Figures 1 and 2 demonstrates a decline in doubleincision repairs and an increase in cortical button alone and cortical button plus interference screw fixation over the course of our study period.…”
Section: Discussionmentioning
confidence: 93%
“…12,17,24,35 Despite biomechanical studies showing fixation superiority of some implants over others, the relative rarity of distal biceps tendon ruptures and the multitude of repair techniques available mean the literature lacks enough power to provide strong clinical evidence on the repair method of choice. 1,35 We examined the largest series of captured distal biceps tendon repair patients within an integrated health care system to determine which repair method results in the best patient outcomes with the fewest rates of complications. Our hypothesis was that repairs performed with a cortical button with an interference screw would produce the best patient outcomes with the lowest rates of complications.…”
mentioning
confidence: 99%
“…However, a direct comparison between suture button and interference screw has been reported, with load to failures ranging from 259 N - 439 N for the cortical button and 131 N - 294 N for the interference screw. Additionally, Arianjam et al compared interference screw to interference screw and cortical button and demonstrated no significant difference between the two loads to failure strengths [ 2 , 3 , 17 - 19 ]. Lastly, Greenberg et al compared the pull-out strength of three anchoring methods and revealed the cortical button was three times as strong as the bone bridge and twice as strong as the Mitek suture anchor (DePuy Mitek, Inc., Raynham, USA) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The (Arianjam et al, 2013) with failure occurring at the tendon-bone interface. This is similar in magnitude to the clamp interface failure in the present study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%